The Association Between Platelet Counts and the Esophageal Varices among Patients with Cirrhosis in Pranangklao Hospital, Thailand - Kanchanauthai, Wichak (Journal of Preventive Medicine Association of Thailand, 2023)
Background: The most common complication in patients with cirrhosis is the occurrence of esophageal varices which can be diagnosed by endoscopic methods. The possible use of Platelet count for the diagnosis of esophageal varices in liver cirrhosis patients has been proposed. Therefore, it would be of great importance to reveal the association between platelet counts and the incidence of esophageal varices in cirrhotic patients. Objective: To study the association between platelet counts and esophageal varices among cirrhotic patients in the Pranangklao Hospital. Methods: This retrospective study was conducted at Pranangklao Hospital between October 2021 and September 2022. The sample size was calculated from the proportional estimation formula as 233 cases. Clinical information and laboratory results were collected and analyzed using the Chi-square test, Fisher exact test, and one-way ANOVA, as applicable. Optimal platelet cut-off values and esophageal varices were checked for sensitivity, specificity, positive predictive value, negative predictive value, positive likelihood ratio, negative likelihood ratio, and area under the receiver operating characteristic curve (AUROC). Results: Of the total 233 patients diagnosed with liver cirrhosis at Pranangklao Hospital, 166 patients had esophageal varices (71.24%); and were further divided into Grade I (57 cases), Grade II (32 cases) and Grade III (77 cases). The correlation analysis found that the occurrence of esophageal varices was significantly associated with platelet count (p<0.001). Patients with cirrhosis and platelets <150,000 /µL were found to be associated with esophageal varices. (sensitivity= 68.7%), specific (specificity= 64.2%), and with ROC area = 0.664 (95%CI = 0.596 – 0.732), likelihood ratio (+) = 1.92, likelihood ratio (-) = 0.488, positive predictive value = 82.6%, and negative predictive value = 45.3%. Conclusion: The platelets <150,000 /µL in patients with cirrhosis and were found to be associated with esophageal varices. Therefore, it could be used as a predictor of the condition.